PSYCHOSOMATIC "ARC" IN THE PSYCHOTHERAPEUTIC PRACTICE - Ivanka Boncheva (Peytchinski Publishing, 2012)
The psychoneuroimmunology, the new brain science and the endocrinology today show a lot of results, with which symptoms are better to understand. The psychotherapeutic practice shows the ways to influence them by encoding the levels of bounding between the physical symptom and the psychological condition. The aim of the study was to show the encoding of the psychosomatic arc within a real psychotherapeutic contact. 59 psychotherapeutic cases are followed. 33 of them were with somatoform disorders and 26 with chronic psychosomatic diseases. Every patient has minimum 12 psychotherapeutic sessions. The treatment is provided on the base of the 5 levels model of the positive psychotherapy.We ascertain the following:1. The most significant moment in the arise of such symptomatic is the gained past experience - "vital concepts"; "coping strategies";2. Unlocking moment for the arise of the affection is the fixed emotion - fear, aggression or depression, specific for the particular morbid pictures;3. Showing the connection between symptom and fixed emotion by the technique "positive interpretation", which unlocks the process of changingThis shows that the psychotherapeutic help is possible only if the patient rethink the psychosomatic arc. Showing the connections between the content of the unconscious, the fixed emotion in behavioral models and the symptom gives the impetus to change.